A rare cause of respiratory distress in infants: tracheal compression due to anomalous course of innominate artery - Yalçinbaş, Yusuf Kenan; Erek, Ersin; Salihoğlu, Ece; Sarioğlu, Ayşe; Sarioğlu, Tayyar (The Turkish Journal of Pediatrics, 2006)
Incomplete vascular ring is a rare congenital vascular anomaly causing tracheal compression. A case of anomalous innominate artery causing tracheal compression and low grade tracheomalacia with remarkable dyspnea and intermittent apnea in a five-month-old infant is reported. Chest X-ray revealed enlarged upper mediastinum. Patent foramen ovale and thymus hyperplasia were detected on echocardiographic examination. Angiography demonstrated left aortic arch with normal arterial branching pattern. Thorax computerized tomography (CT) revealed tracheal compression of more than 50% at innominate artery level and aberrant position of the hyperplastic thymus. Operation was planned for subtotal thymectomy and relocation of innominate artery in order to relieve tracheal obstruction. Postoperative thorax CT demonstrated satisfactory relief of tracheal compression. Patient was discharged from hospital on sixth postoperative day in good condition. On clinical follow-up he is completely asymptomatic without any signs of dyspnea or intermittent reflex apnea. In severely symptomatic cases, surgical treatment offers excellent results.